Use of individual relative thresholds to assess acceleration in young soccer players according to initial speed - Martinez-Cabrera, F. I.; Núñez-Sánchez, F. J.; Losada, J.; Otero-Esquina, C.; Sánchez, H.; De Hoyo, M. (The Journal of Strength and Conditioning Research, 2018)
The aims of the current study were (a) to analyze the characteristics of acceleration efforts using individual relative thresholds according to the initial speed during official matches in elite young soccer players according to player position and (b) to compare the differences between absolute and relative thresholds in assessing high-intensity acceleration. Player acceleration profiles were assessed using an individual relative threshold based on their acceleration capacity at different initial speeds (standing, 6, 10.8, and 15 km/h), and the number of accelerations (>75% of the maximal acceleration) performed during soccer matches was divided into 3 categories attending to the initial speed. (S1 = 0-7 km/h; S2 = 7.1-14 km/h; and S3 = =14.1 km/h. Within-group analyses showed that the number of accelerations performed in each category was higher when the effort started from a static or walking position than at moderate- or high-intensity running (S1 > S2 > S3; very likely to almost certain). Between-group analyses revealed substantial differences between some playing positions according to initial speed. In S1 and S3, central defenders had the lowest number of accelerations (likely to almost certain), whereas midfielders had the greatest number of high-intensity accelerations in S1 and S2. There were also substantial differences between the other playing positions (possibly to almost certain). Regarding relative and absolute thresholds (>3 m/s), the results showed that absolute threshold overestimated the number of high-intensity accelerations compared with the individual relative threshold in S1 and underestimated the results in S2 and S3 (almost certain). The use of an individual relative threshold to measure acceleration demands allows to distinguish between the numbers of accelerations in function of the initial speed and playing positions. In addition, the absolute acceleration threshold could overestimate or underestimate the acceleration demands in young soccer players as a function of the initial speed. Then, the absolute acceleration thresholds should be taken with caution in the assessment of acceleration activities.